The Application of Combined Immune Checkpoint Inhibitor Modalities in Previously Treated Non-Small Cell Lung Cancer Patients and the Associations Thereof With the Lung Immune Prognostic Index - Zhang, Ting; Yang, Xue; Zhao, Jing; Xia, Lixia; Wang, Qiyuan; Jin, Rui; Zhou, Lingxiao; Zhang, Bin; Zhao, Jun; Li, Huijie; Li, Wen; Xia, Yang (Frontiers in Oncology, 2021)
Background Immune checkpoint inhibitor (ICI) monotherapy remains the standard of care for patients with previously treated non-small cell lung cancer. However, few reports have compared the clinical benefits of second-line ICIs alone with those of ICIs combined with other therapies, including anti-angiogenesis therapy or chemotherapy. Methods Patients with previously treated advanced non-small cell lung cancer who received ICIs were retrospectively reviewed. The progression-free survival (PFS), overall survival, objective response rate, disease control rate, and safety were assessed. Complete blood cell counts and serum lactate dehydrogenase (LDH) levels were measured before and after ICI treatment. Results Of 120 patients, 75 were treated with ICI monotherapy, 26 with ICIs plus anti-angiogenic therapy (ICI+A), and 19 with ICIs plus chemotherapy (ICI+C). The objective response rate was significantly higher in the ICI+C group (57.9%) than ICI monotherapy (26.3%) and ICI+A (31.8%) groups. The depth of response was significantly greater in the ICI+C (-35.1%) than ICI+A (−2.04%) and ICI monotherapy (3.963%) groups. ICI+C afforded a better PFS compared with the ICI monotherapy and ICI+A groups (8.5 vs. 4.6 and 4.1 months, respectively). Notably, the pre- and post-treatment peripheral neutrophil/lymphocyte ratios and serum LDH levels were negatively correlated with the PFS of the entire cohort. More importantly, the pretreatment lung immune prognostic index (neutrophil/lymphocyte ratio ≥ 4 and LDH level ≥ upper limit of normal) satisfactorily predicted the responses to ICI-based strategies. Adverse events (AEs) occurred in 65.3%, 92.3%, and 94.7% of patients in the ICI monotherapy, ICI+A, and ICI+C groups, respectively. Grade 3–5 AEs were more common in the combination therapy groups (ICI+A, 19.2%; ICI+C, 21%; ICI monotherapy, 4%). Conclusion In second-line settings and beyond, ICIs combined with chemotherapy prolonged survival, with tolerable AEs. Addition of anti-angiogenic agents to ICIs did not afford any additional benefits. Further prospective studies are warranted.